Human-Mimic Submuscular and Premuscular Irradiated Rat Model: Histologic Characteristics of the Capsule Tissue in Contact with the Breast Implant - Hyung Bae Kim; Se Young Han; Jin Sup Eom; Hyun Ho Han (The Breast Journal)
Background. In this study, we established two rat models that mimic human submuscular and premuscular breast reconstruction. We analyzed the capsule formation according to surgical techniques and adjacent tissues, including the chest wall tissues, such as the ribs and acellular dermal matrices (ADMs) that come in contact with silicone implants. Methods. This study consisted of experiments on 12 Sprague–Dawley rats that underwent implant reconstruction using ADM. They were divided into two groups: rats that underwent dual-plane implantation (n = 6; group 1) and those that underwent premuscular implant insertion (n = 6; group 2). All rats were irradiated with 35 Gy of fractionated radiation. Three months after surgery, the histology and immunochemistry of the capsule tissues of the ADM, muscle, and chest wall were analyzed. Results. Overall capsule thickness was thicker in group 1. Based on the tissue in contact with the silicone implant, ADM had a thinner capsule, less inflammation, less fibrosis, and less vascularization than the muscle and chest wall tissues. Conclusions. This study described two rat models of clinically relevant implant-based breast reconstruction using a submuscular and premuscular plane, ADM, and irradiation. Overall, the premuscular implantation rat model was associated with a thinner capsule. The ADM in contact with the silicone implant, even after irradiation, had superior protection from radiation compared with the other tissues.